Measuring and Evaluating Sharia Business Unit Spin-Off in Indonesia Using RBBR Model - Rukminastiti, Atika Masrifah; Rifai, Muhammad Rizqi (Li Falah: Journal of Islamic Economics and Business, 2024)
This study aims to measure and evaluate the performance of sharia business units that have spun off into sharia commercial banks in Indonesia, with an emphasis on the effectiveness of implementing the Risk-Based Bank Rating model. In addition, the study is driven by the regulatory mandate of the Sharia Banking Law and the industry's need for institutional strengthening after the spin-off. The research method uses a quantitative-descriptive approach by applying four main indicators in the RBBR model: risk profile, good corporate governance, profitability, and capital. Secondary data was obtained from the annual financial reports of Islamic banks resulting from spin-offs in the 2010–2022 period, which were then analysed comparatively to assess the differences in performance before and after the spin-off. The results show that spin-offs generally positively impact capitalisation and profitability, although improving governance quality and risk mitigation still face significant challenges. These findings provide input for regulators, particularly the Financial Services Authority (OJK), to refine spin-off policies so that they are oriented towards fulfilling legal obligations and increasing the competitiveness and stability of the Islamic banking system in Indonesia. The implications of this research emphasise the importance of risk management strengthening strategies, product diversification, and operational efficiency optimisation so that BUS after spin-offs can compete sustainably with conventional and full Islamic banks.